The Transcription Factor Tcf1 Contributes to Normal NK Cell Development and Function by Limiting the Expression of Granzymes - Beena Jeevan-Raj (Cell Reports, 2017)
The transcription factor Tcf1 is essential for the development of natural killer (NK) cells. However, its precise role has not been clarified. Our combined analysis of Tcf1-deficient and transgenic mice indicated that Tcf1 guides NK cells through three stages of development. Tcf1 expression directed bone marrow progenitors toward the NK cell lineage and ensured the survival of NK-committed cells, and its downregulation was needed for terminal maturation. Impaired survival of NK-committed cells was due to excessive expression of granzyme B (GzmB) and other granzyme family members, which induced NK cell self-destruction during maturation and following activation with cytokines or target cells. Mechanistically, Tcf1 binding reduced the activity of a Gzmb-associated regulatory element, and this accounted for the reduced Gzmb expression in Tcf1-expressing NK cells. These data identify an unexpected requirement to limit the expression of cytotoxic effector molecules for the normal expansion and function of NK cells.